Human-like hip joint loading in Australopithecus africanus and Paranthropus robustus. Issue 121 (August 2018) - Ryan, Timothy M.; Carlson, Kristian J.; Gordon, Adam D.; Jablonski, Nina; Shaw, Colin N.; Stock, Jay T.
Abstract: Adaptations indicative of habitual bipedalism are present in the earliest recognized hominins. However, debate persists about various aspects of bipedal locomotor behavior in fossil hominins, including the nature of gait kinematics, locomotor variability across different species, and the degree to which various australopith species engaged in arboreal behaviors. In this study, we analyze variation in trabecular bone structure of the femoral head using a sample of modern humans, extant non-human hominoids, baboons, and fossil hominins attributed to Australopithecus africanus, Paranthropus robustus, and the genus Homo . We use μCT data to characterize the fabric anisotropy, material orientation, and bone volume fraction of trabecular bone to reconstruct hip joint loading conditions in these fossil hominins. Femoral head trabecular bone fabric structure in australopiths is more similar to that of modern humans and Pleistocene Homo than extant apes, indicating that these australopith individuals walked with human-like hip kinematics, including a more limited range of habitual hip joint postures (e.g., a more extended hip) during bipedalism. Our results also indicate that australopiths have robust femoral head trabecular bone, suggesting overall increased loading of the musculoskeletal system comparable to that imposed by extant apes. These results provide new evidence of human-like bipedal locomotion in Pliocene hominins, even while other aspects of their musculoskeletal systems retain ape-like characteristics.